Factors Affecting Purchase Intention and Social Media Publicity of Green Products: The Mediating Role of Concern for Consequences. (25th August 2017) - Zahid, Muhammad Mohsin; Ali, Bakhtiar; Ahmad, Muhammad Shakil; Thurasamy, Ramayah; Amin, Naila
Abstract: The emerging concern for the environment, particularly in consumer products, has grabbed the attention of both practitioners and academics equally. With the aid of new communication tools such as social media, the concern for the environment has been widely shared. The motivation behind consumer behaviour towards environmentally friendly green products is different compared to general non‐green products. The present study explored the factors that determine the purchase intention of green products and publicity on social media. The mediating role of concern for consequences and the moderating role of economic factors was also analysed. A total of 347 consumers were sampled in the present study by means of systematic sampling from cosmetic stores. Structural equation modelling using SmartPLS 3 software was employed to analyse the data of the present study. Notably, the mediating role of concern for consequences and economic factor are supported. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment